2016
DOI: 10.3832/ifor1866-008
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage and soil property changes following afforestation in mountain ecosystems of the Western Rhodopes, Bulgaria

Abstract: Land-use changes and afforestation activities are widely recognized as possible measures for mitigating climate change through carbon sequestration. The present study was conducted to evaluate the effect of afforestation on (i) soil physical and chemical properties and soil carbon stocks in four mountain ecosystems and (ii) whole ecosystem carbon storage. The four experimental sites, situated in the Western Rhodope Mountains (Bulgaria) were characterized by typical forest-related land-use conversions. The four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
7
10
0
Order By: Relevance
“…(2018) (1.03–1.11%) in the roadside plantation of north-western Haryana, India. A variation was observed in the organic carbon content in the same layer of soil for different sample areas; this is similar to the findings of Zhiyanski et al. (2015) .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(2018) (1.03–1.11%) in the roadside plantation of north-western Haryana, India. A variation was observed in the organic carbon content in the same layer of soil for different sample areas; this is similar to the findings of Zhiyanski et al. (2015) .…”
Section: Discussionsupporting
confidence: 87%
“…Soil organic carbon has an important function in the carbon cycle; hence, its presence and availability significantly influence climate change ( Smith, 2004 ; Vaccari et al., 2011 ). Our study found an organic carbon content of 2.76–7.6%, 2.1–6.51% and 1.64–6.34% at depths of 0–15 cm, 15–30 cm, and 30–45 cm respectively in all the studied sample areas which are higher than 0.35–4.14% in afforested land as reported by Zhiyanski et al. (2015) and Arya et al.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…SOC concentration in the Ap horizon in forest soil decreased during the study period by 0.9 mg kg -1 , while the losses in unfertilised soil in crop rotation were three times as high (2.7 mg kg -1 ). Similarly, Zhiyanski et al (2015) reported that in Bulgaria afforestation by coniferous species helped accumulate and preserve soil carbon, but even several decades after the conversion from arable cropland or abandoned land to forest land use, this effect was expressed only weakly and could not compensate the organic carbon loss due to previous active cultivation. Also in Northern Europe (Barcena et al 2014), afforestation with conifers for the periods <30 years and >30 years since afforestation revealed a shift from initial loss to later gain of SOC.…”
Section: Arable Land Transformation Into Pine Afforested Landmentioning
confidence: 99%
“…Insufficient long‐term organic matter input to the soil can inhibit carbon (C) sequestration and nitrogen (N) fixation, reducing the capacity of soil C and N pools. Such constant and persistent low nutrient contents and water supplies reduce the biological production of aboveground plants and vegetation coverage, which would diminish C inputs to the soil and inactivate nutrient cycling in mountainous and hilly areas with poor soil (Potthast et al, 2012; Shimoda and Koyanagi, 2017; Willcock et al, 2014; Zhiyanski et al, 2016). Ecologists and agronomists have tried to increase soil C inputs and promote geochemical cycling in a variety of ways to prevent soil infertility, such as by adding high‐efficiency C sources (Yu et al, 2018), microbial fertilizers (Wu et al, 2018; Igiehon and Babalola, 2018), and soil improvement agents (Dannehl et al, 2016; Kathijotes et al, 2016); planting green manure (GM); and covering the soil with straw (He et al, 2018).…”
mentioning
confidence: 99%